(untitled) (Baghdad Science Journal, 2022)
A theoretical and protection study was conducted of the corrosion behavior of carbon steel surface with different concentrations of the derivative (Quinolin-2-one), namely 7-Ethyl-4-methyl-1-[(4-nitro-benzylidene)-amino]-1H-quinolin-2-one (EMNQ2O). Theoretically, Density Functional Theory (DFT) of B3LYP/ 6-311++G/ 2d, 2p level was carried out to calculate the geometrical structure, physical properties and chemical inhibition chemical parameters, with the local reactivity in order to predict both the reactive centers and to know the possible sites of nucleophilic and electrophilic attacks, in vacuum and two solvents (DMSO and H2O), all at the equilibrium geometry. Experimentally, the inhibition efficiencies (%IE) in (3.5% NaCl) and (0.5M HCl) solutions were studied using potentiometric polarization measurements. The results revealed that the (%IE) in the salty solution (94.98%) is greater than that in the acidic solution (81.40%). The thermodynamic parameters obtained, supported the physical adsorption mechanism and the adsorption followed the Langmuir adsorption isotherm. The surface changes of the carbon steel were studied using SEM (Scanning Electron Microscopy) and AFM (Atomic Force Microscopy) techniques.